Answer:
x + 3y = -15
Explanation:
There are 2 ways to find this equation:
The first way: We have: y = ax + b (this is the line, right?)
The line is through the point (-6, -3) so we have:
-3 = (-6)a + b (1)
The line is also through the point (-9, -2) so we have:
-2 = (-9)a + b. (2)
From (1) and (2) we get a equals -1/3, b equals -5. Then:
![y=-(1)/(3) x - 5](https://img.qammunity.org/2023/formulas/mathematics/college/dzdsncyxowkab6dw081cpg3fg9bf9ft77e.png)
<=>
![x + 3y=-15](https://img.qammunity.org/2023/formulas/mathematics/college/4cxelgqg3fkwg7z5evcpk7qee3luo7mhr7.png)
The second way:
Let A(-6, -3) and B(-9, -2), then AB = (-3, 1).
=> The normal vector of this line is n = (1, 3).
The line that is through the points A(-6, -3) and B(-9, -2), and has the normal vector n=(1, 3) has the equation:
![1(x+6) +3(y+3)=0\\x+3y +15=0\\x+3y=-15](https://img.qammunity.org/2023/formulas/mathematics/college/3sk146oeipd1vrnq7gmamqciad63zr2477.png)